2019
DOI: 10.1371/journal.pone.0223994
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing a field of research: A methodology of systematic scientometric reviews

Abstract: Systematic scientometric reviews, empowered by computational and visual analytic approaches, offer opportunities to improve the timeliness, accessibility, and reproducibility of studies of the literature of a field of research. On the other hand, effectively and adequately identifying the most representative body of scholarly publications as the basis of subsequent analyses remains a common bottleneck in the current practice. What can we do to reduce the risk of missing something potentially significant? How c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
574
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 776 publications
(584 citation statements)
references
References 54 publications
2
574
0
8
Order By: Relevance
“…CiteSpace is an information visualization software system suitable for multivariate, timesharing, and dynamic complex network analysis [11,17,72,86,87]; it takes a set of bibliographic records as its input and models the intellectual structure of the underlying domain in terms of a synthesized network based on a time series of networks derived from each year's publications. CiteSpace supports several types of bibliometrics studies, including collaboration network analysis, co-word analysis, ACA, document co-citation analysis, text and geospatial visualizations.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…CiteSpace is an information visualization software system suitable for multivariate, timesharing, and dynamic complex network analysis [11,17,72,86,87]; it takes a set of bibliographic records as its input and models the intellectual structure of the underlying domain in terms of a synthesized network based on a time series of networks derived from each year's publications. CiteSpace supports several types of bibliometrics studies, including collaboration network analysis, co-word analysis, ACA, document co-citation analysis, text and geospatial visualizations.…”
Section: Plos Onementioning
confidence: 99%
“…The impact of the introduction of new knowledge on the fundamental network structure of existing research fields is a crucial aspect of the development of scientific activities. A major form of creative work is to bridge previously disjoint bodies of knowledge [10][11][12][13]. Chen proposed a predictive analytic model-structural variation analysis (SVA) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Citation bursts on the other hand refer to suddenly increasing citation frequency which indicates that the report focuses on a key issue in the eld. [16] Table 2 shows references and corresponding information for the top 10 strongest citation bursts.…”
Section: The Analysis Of Key Literaturementioning
confidence: 99%
“…Bibliometrics is a statistical and quantitative method used to analyse publications and visualise networks associated with a body of literature (e.g., [8,9]). Such an approach is being employed in systematic reviews and can potentially reveal unknown relations between different areas of research, and such findings have been demonstrated in literature-based discovery (e.g., [10][11][12]) or the study of citation impact indicator (e.g., [13]). In this work, a simplified scientometric approach (a subfield of bibliometrics with a focus on analysing the scientific literature) has been applied to the available literature on gunshot residue (GSR) to identify patterns and trends in, for example, keyword, co-authorship, collaborative networks, country of origin and citations rates.…”
Section: Introductionmentioning
confidence: 99%